Wisdom at the Interface between God and Humans - Krusche, Marcel, (Schöningh, Fink and mentis Religious Studies, Theology and Philosophy E-Books Online, Collection 2026., 2026)
At the centre of the anthology are Gen 2-3 and Ez 28:11-19, from which concepts of wisdom and the formation of knowledge concerning the relationship between God and man are examined. The positions identified are categorised within larger Old Testament, ancient Near Eastern and early Jewish horizons. The aim is, on the one hand, to better understand the concept of wisdom or knowledge in Gen 2-3 and Ezek 28 and, on the other hand, to shed light on the superhuman and divine dimensions of wisdom and knowledge in the various textual areas and cultures. The contributions are based on the following key questions: - What makes wisdom and cognition/knowledge a divine or superhuman quality? - How can people attain divine wisdom and participate in it? - What effects and consequences do wisdom and insight/knowledge have for people? - How and to what extent do wisdom and cognition/knowledge affect the relationship between God and man?